(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Amino acids play important roles in organisms to sustain in living state and perform as body constituents, enzymes and antibodies. At insalubrious situations, use of amino acids derivatives as drugs in the maintenance of normal health is better choice than common unnatural synthetic drugs. This is due to the fact that the amino acids derivatives may be more bio-compatible, biodegradable and eliminate easily than others. In this sense we have made an effort and report herein the synthesis of N-2-(4-chlorophenyl) acetyl amino alcohols synthesised by reduction of N-2-(4-chlorophenyl)acetyl derivatives of (S)-amino acids such as (S)-phenylalanine, (S)-alanine, (S)-methionine, (S)-leucine, (S)-tryptophan and (S)-proline. These newly synthesized amino acids derivatives were analysed by proton, carbon-13 NMR and FT-IR spectroscopy. The composition of solid derivatives was determined by elemental analysis. Further, antimicrobial activities of these derivatives were assessed on usual bacteria K. aerogenes, E. coli, S. aureus and P. desmolyticum and fungi A. flavus and C. albicans. The compounds were witnessed moderate activity than authorised antibacterial and fungal agents Ciprofloxacin and Fluconazole respectively. The antimicrobial studies also revealed that, these derivatives could be better antifungal agents than antibacterial agents. Finally we compared the experimental results of antimicrobial activities with docking studies.